Developmental Dynamics of Emotion and Cognition Processes in Preschoolers. Issue 1 (23rd August 2012) - Blankson, A. Nayena; O'Brien, Marion; Leerkes, Esther M.; Marcovitch, Stuart; Calkins, Susan D.; Weaver, Jennifer Miner
<x xml:space="preserve">Abstract</x> Dynamic relations during the preschool years across processes of control and understanding in the domains of emotion and cognition were examined. Participants were 263 children (42% non‐White) and their mothers who were seen first when the children were 3 years old and again when they were 4. Results indicated dynamic dependence among the processes studied. Specifically, change in cognitive processes of control and understanding were dependent upon initial levels of the other processes. Changes in emotion control and understanding were not predicted by earlier performance in the other processes. Findings are discussed with regard to the constructs of control and understanding and the developmental interrelations among emotion and cognitive processes.